Doll Simulation for Sexual Education To Improve Knowledge of Personal Safety Skills - Wijayanti, Kurnia; Astuti, Indra Tri; Wahyuningsih, Tri; Khasanah, Nopi Nur (International Journal of Psychosocial Rehabilitation, 2020)
Sexual violence against children, especially those aged 5-17 years, has increased every year with culprits mainly consisting of the people closest people to the victims (80.23%). Sexual violence experienced by children can cause fear, excessive anxiety, disruption of self-concept, a feeling of deep trauma, the deterioration of the child's physical and mental health condition and can take place in the long term. Therefore the importance of providing knowledge about personal safety skills, so that children understand how they can protect themselves, recognize dangerous situations, and what to do. The purpose of this study was to determine the effectiveness of doll simulation of sexual education on personal safety skills knowledge in preschool children. This quantitative study used the pre-experiment method and a pre-test and post-test research design without a control group. This study used non-probability sampling with total sampling, namely a group of 17 children aged 5-6 years. The instrument used was a knowledge questionnaire about personal safety skills consisting of 17 items that had been tested for validity and reliability. Data analysis was conducted using the Wilcoxon test. The results of this study indicate that doll simulation is effective in increasing knowledge about personal safety skills in pre-school children with a p value of 0.008 (p